Changes in the amino acid sequence of the recombinant human factor VIIa analog, vatreptacog alfa, are associated with clinical immunogenicity. (13th October 2015) - Mahlangu, J. N.; Weldingh, K. N.; Lentz, S. R.; Kaicker, S.; Karim, F. A.; Matsushita, T.; Recht, M.; Tomczak, W.; Windyga, J.; Ehrenforth, S.; Knobe, K.; ,
Summary: Background: Vatreptacog alfa, a recombinant human factor VIIa (rFVIIa) analog developed to improve the treatment of bleeds in hemophilia patients with inhibitors, differs from native FVIIa by three amino acid substitutions. In a randomized, double‐blind, crossover, confirmatory phase III trial (adept ™ 2), 8/72 (11%) hemophilia A or B patients with inhibitors treated for acute bleeds developed anti‐drug antibodies (ADAs) to vatreptacog alfa. Objectives: To characterize the formation of anti‐vatreptacog alfa ADAs in hemophilia patients with inhibitors. Methods/patients: This was a post hoc analysis of adept ™ 2. Immunoglobulin isotype determination, specificity analysis of rFVIIa cross‐reactive antibodies, epitope mapping of rFVIIa single mutant analogs and pharmacokinetic (PK) profiling were performed to characterize the ADAs. Results: Immunoglobulin isotyping indicated that the ADAs were of the immunoglobulin G subtype. In epitope mapping, none of the rFVIIa single mutant analogs (V158D, E296V or M298Q) contained the complete antibody epitope, confirming that the antibodies were specific for vatreptacog alfa. In two patients, for whom PK profiling was performed both before and after the development of ADAs, vatreptacog alfa showed a prolonged elimination phase following ADA development. During the follow‐up evaluation, the rFVIIa cross‐reactivity disappeared after the last vatreptacog alfa exposure, despite continued exposure to rFVIIa as part of standard care. Conclusions: Results from the vatreptacog alfa phase III trial demonstrate that the specific changes made, albeit relatively small, to the FVIIa molecule alter its clinical immunogenicity.